Wear Resistance Enhancement of AISI D3 Tool Steels by Cryogenic Treatment: A Review - Singh, Harvinder; Singh, Swarn; Goyal, Aneesh (Asian Review of Mechanical Engineering, 2018)
The aim of this study is to reveal the enhancement of wear resistance of AISI D3 Tool Steel by Cryogenic Treatment. Cryogenic Treatment is often referred as Cryotreatment, is an add-on process to the conventional heat treatment. In the experimentation process, samples of AISI D3 tool steel were taken in batches out of which some samples were treated with conventional heat treatment (QT) whereas other were cryogenically treated (QCT) at 77 K for a period of 24 hrs. Dry sliding wear test were carried out on Pin on Disk machine. The input parameters are Load (N), and sliding velocity (V). Trials were performed in combination of above said parameters. Later on SEM was been carried on the worked samples so as to compare the microstructural changes between the conventional heat treated samples and cryogenically treated samples.